Maturing Professional Selfhood through Body Mapping - Colleen Maykut (San Beda University, 2021)
Nursing education's fundamental goal is to prepare students to effectively transition into practice. Success in this endeavor occurs when the student has a clear sense of themselves as a professional in relationship with their peers and grounded in disciplinary knowledge. Faculty must intentionally create opportunities for students to explore and mature their professional selfhood (PSH) to assist in a smooth transition from academia to practice. Educational strategies which enhance the awareness and continued development of PSH as a birthplace for professional identity may enable the graduate to navigate the healthcare system, mitigate ethical dilemmas, and enhance the quality of life for those they care for and themselves. Aesthetic narratives could be utilized to engage students in the analysis of their PSH as an alternative beyond the dominant text as an expression.